The fecal microbiota of wild and captive raptors - Oliveira, Bruno C. M. [UNESP]; Murray, Maureen; Tseng, Florina; Widmer, Giovanni (Bmc, 2020)
Background The microorganisms populating the gastro-intestinal tract of vertebrates, collectively known as microbiota, play an essential role in digestion and are important in regulating the immune response. Whereas the intestinal microbiota in humans and model organisms has been studied for many years, much less is known about the microbiota populating the intestinal tract of wild animals. Results The relatively large number of raptors admitted to the Tufts Wildlife Clinic on the Cummings School of Veterinary Medicine at Tufts University campus provided a unique opportunity to investigate the bacterial microbiota in these birds. Opportunistic collection of fecal samples from raptors of 7 different species in the orders Strigiformes, Accipitriformes, and Falconiformes with different medical histories generated a collection of 46 microbiota samples. Based on 16S amplicon sequencing of fecal DNA, large beta-diversity values were observed. Many comparisons exceeded weighted UniFrac distances of 0.9. Microbiota diversity did not segregate with the taxonomy of the host; no significant difference between microbiota from Strigiformes and from Accipitriformes/Falconiformes were observed. In contrast, in a sample of 22 birds admitted for rehabilitation, a significant effect of captivity was found. The change in microbiota profile was driven by an expansion of the proportion of Actinobacteria. Based on a small number of raptors treated with anti-microbials, no significant effect of these treatments on microbiota alpha-diversity was observed. Conclusions The concept of meta-organism conservation, i.e., conservation efforts focused on the host and its intestinal microbiome has recently been proposed. The observed effect of captivity on the fecal microbiota is relevant to understanding the response of wildlife to captivity and optimizing wildlife rehabilitation and conservation efforts.
Keywords: Raptor; Fecal microbiota; Rehabilitation; Actinobacteria; 16S amplicon sequencing